PERBANDINGAN INFORMASI LAPORAN KEUANGAN SEBELUM DAN SESUDAH IFRS DALAM PERUSAHAAN SEKTOR PROPERTI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Syafruddin Syafruddin (Universitas Riau Kepulauan, 2016)
This study aimed to compare the financial statements of the information before and after IFRS in the property sector companies listed on the Indonesia Stock Exchange. The results showed that the differences in financial reporting information before and after IFRS. While the conclusions that can be drawn is that there is a significant difference in the value of fixed assets, equity, net income before and after IFRS while the value of liquidity and gearing showed no significant difference before and after IFRS in the property sector companies listed on stock exchanges in Indonesia.